1994
DOI: 10.1111/j.1600-0749.1994.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Melanoma Incidence: Putatively Explainable by Retrotransposons Experimental Contributions of the Xiphophorine Gordon‐Kosswig Melanoma System

Abstract: The worldwide accelerating increase of neoplasia in humans is difficult to explain. We use the Xiphophorus tumor model to approach this problem by melanoma provocation with X-rays. Melanoma develops following inappropriate expression of x-erb B-conducted developmental genes and their controllers. These oncodeterminants are inherited according to Mendelian rules. We detected a new type of oncodeterminants that, following a single treatment of embryos with X-rays, generates a self-generating non-Mendelian melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…4a). This pattern is different from the one reported from radioactive in situ hybridization analysis with the original XIR-1 probe (Anders et al 1994), indicating some structural differences between XIR-1 and the XIR LTR-like sequence that we isolated from cosmid D18 097. The FISH signal was conspicuously located at the terminal region of the long arm and at least 20 metaphase spreads were evaluated to confirm the near-terminal location of the XIR probe.…”
Section: Clustered Organization Of Xir Repeats On the Y Chromosomecontrasting
confidence: 80%
See 2 more Smart Citations
“…4a). This pattern is different from the one reported from radioactive in situ hybridization analysis with the original XIR-1 probe (Anders et al 1994), indicating some structural differences between XIR-1 and the XIR LTR-like sequence that we isolated from cosmid D18 097. The FISH signal was conspicuously located at the terminal region of the long arm and at least 20 metaphase spreads were evaluated to confirm the near-terminal location of the XIR probe.…”
Section: Clustered Organization Of Xir Repeats On the Y Chromosomecontrasting
confidence: 80%
“…Southern blot analysis using low-stringency as well as high-stringency washes revealed that the XIR repeat is highly reiterated within the genome of both males and females of X. maculatus from Rio Jamapa and from Rio Usumacinta (Fig. 2a) as described for the original XIR LTR (Anders et al 1994). …”
Section: Isolation and Characterization Of Sex-chromosomal Sequencesmentioning
confidence: 95%
See 1 more Smart Citation
“…Because we wished to generate a representative genomic library, the use of highly repeated DNA elements as hooks in our cloning vectors was critical. DNA sequencing of some regions of X. maculatus revealed the presence of several different and varied repetitive elements (Anders et al, 1994;Nanda et al, 2000;Froschauer et al, this issue). For our first library construction we chose the XIR-1 repeat, originally characterized by Anders et al (1994), that is the 5Ј region of a retroviral long terminal repeat (LTR); characterization of the repeat indicated this element was widely distributed over the fish genome.…”
Section: Construction Of Fish Yacs Via Tar Cloningmentioning
confidence: 88%
“…Xiphophorus fishes have been used in research of the immune system for well over fifty years (Kallman 1958(Kallman , 1964. Backcrosses between certain strains of helleri and maculatus can result in fish that develop malignant melanoma, among other diseases (Anders et al 1994;Kazianis et al 2001). The availability of inbred strains and the initial characterization of MHC DAB and DXB genes in Xiphophorus make the genus an excellent system in which to study evolutionary dynamics of MHC class II genes.…”
mentioning
confidence: 99%